Error Analysis of Using Simple Past Tense at Tenth Grade of SMA 1 Kuok: Pengabdian - Wida Rianti; Nurbayti (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to analyze students' grammatical errors in using the Simple Past Tense when writing narrative texts at SMA 1 Kuok. A total of 32 tenth-grade students were involved in this study, which applied a descriptive qualitative method. The data were collected through a writing test where students were asked to compose a personal narrative using the Simple Past Tense. Error analysis was conducted using the Surface Strategy Taxonomy by Dulay et al., which categorizes errors into omission, addition, misformation, and misordering. The results showed 102 total errors, with misformation as the most dominant type (48.04%), followed by addition (26.47%), omission (13.73%), and misordering (11.76%). Most students made errors related to incorrect verb forms, especially irregular verbs and auxiliary usage. These findings indicate that many students have not fully mastered the concept and application of Simple Past Tense in context. The study suggests that grammar instruction should be more contextual and practical, integrating meaningful writing tasks and interactive strategies to help students internalize grammar rules.